Blood lead levels in a group of children: the potential risk factors and health problems - Mones M. AbuShady; Hanan A. Fathy; Gihan A. Fathy; Samer abd el Fatah; Alaa Ali; Mohamed A. Abbas (Elsevier, 2017)
Objective: To investigate blood lead levels in schoolchildren in two areas of Egypt to understand the current lead pollution exposure and its risk factors, aiming to improve prevention politicies. Subjects and method: This was a cross-sectional study in children (n = 400) aged 6-12 years recruited from two areas in Egypt (industrial and urban). Blood lead levels were measured using an atomic absorption method. Detailed questionnaires on sources of lead exposure and history of school performance and any behavioral changes were obtained. Results: The mean blood lead level in the urban area of Egypt (Dokki) was 5.45 ± 3.90 μg/dL, while that in the industrial area (Helwan) was 10.37 ± 7.94 μg/dL, with a statistically significant difference between both areas (p < 0.05). In Dokki, 20% of the studied group had blood lead levels ≥ 10 μg/dL, versus 42% of those in Helwan. A significant association was found between children with abnormal behavior and those with pallor with blood lead level ≥ 10 μg/dL, when compared with those with blood lead level < 10 μg/dL (p < 0.05). Those living in Helwan area, those with bad health habits, and those living in housing with increased exposure were at a statistically significantly higher risk of having blood lead level ≥ 10 μg/dL. Conclusion: Lead remains a public health problem in Egypt. High blood lead levels were significantly associated with bad health habits and housing with increased exposure, as well as abnormal behavior and pallor. Resumo: Objetivo: Investigar os níveis de chumbo no sangue (NCSs) em crianças em idade escolar em duas áreas do Egito para entender a atual exposição à poluição por chumbo e seus fatores de risco, para melhorar as políticas de prevenção. Indivíduos e método: Esse foi um estudo transversal em crianças (400) com idades entre 6-12 anos recrutadas de duas áreas no Egito (industrial e urbana). Os NCSs foram medidos por um método de absorção atômica. Foram obtidos questionários detalhados sobre as fontes de exposição ao chumbo e o histórico de desempenho escolar e quaisquer alterações comportamentais. Resultados: O NCS na área urbana do Egito (Dokki) foi 5,45 ± 3,90 μg/dL, ao passo que na área industrial (Helwan) foi 10,37 ± 7,94 μg/dL, com uma diferença significativa entre ambas as áreas (p < 0,05). Na área de Dokki, 20% do grupo estudado apresentaram NCSs ≥10 μg/dL, ao passo que na área de Helwan foi 42%. Foi encontrada uma associação significativa entre as crianças com comportamento anormal e aquelas com palidez com NCS ≥ 10 μg/dL, em comparação àquelas com NCS < 10 μg/dL (p < 0,05). Aquelas que moram na área de Helwan aquelas com hábitos de saúde ruins e aquelas que moram em moradias com maior exposição estiveram significativamente em alto risco de apresentar NCS ≥ 10 μg/dL. Conclusão: O chumbo ainda é um problema de saúde pública no Egito. Altos NCSs foram significativamente associados a hábitos de saúde ruins e moradia com maior exposição, bem como, comportamento anormal e palidez. Keywords: Blood lead levels, Children, Lead exposure, Abnormal behavior, Short stature, Egypt, Palavras-chave: Níveis de chumbo no sangue, Crianças, Exposição ao chumbo, Comportamento anormal, Baixa estatura, Egito